NON-PHAR THE RELATIONSHIP OF FAMILY SUPPORT WITH COMPLIANCE WITH ANTI-TUBERCULOSIS MEDICINE (OAT) IN TB PATIENTS IN MALANG DISTRICT - Anggar Widyahadi; Ratna Roesardhyati (Indonesian Journal of Health Care Management, 2021)
Tuberculosis is a major health problem in the community. Tuberculosis is ranked first as the cause of death due to infectious diseases. Therefore, compliance is required to take medication for the healing process so that it can break the chain of transmission. The purpose of this study was to determine the relationship of family support with adherence to taking anti-tuberculosis drugs (OAT) in TB patients.The design of this study used a correlational method with a cross sectional approach on 61 respondents with a purposive sampling technique in three health centers under the Malang District Health Office in February 2019. Data collection used a family support questionnaire and medication compliance questionnaire. Data analysis used univariate analysis and spearman test in bivariate analysis.The results of the percentage of respondents who have good support 82%, enough support 10%, and support less 8%. The percentage of respondents who obeyed was 89%, and did not comply with 11%. The Spearman test results obtained p value <0.001 which is smaller than 0.05 and r value (coefficient correlation) 0.784.The statistical calculation that has been done has a meaningful meaning or there is a relationship between the family support variable and the medication compliance variable. So it is recommended to involve families in the TB treatment process.